The study of knowledge and attitude of new coming residents in cardiopulmonary resuscitation in Tehran University of Medical Sciences, 1377-78 - Haj Zeinali AM (Tehran University Medical Journal, 2000)
Cardiopulmonary resuscitation (CPR) is one of the most important skills that every body must know it in medical services. In educational hospitals, the (Newly-arrived residents are in first cell for management of victims, specially in emergency rooms and at nights. Their knowledge and ability for successful CPR have a direct relation with prevalence of total mortality and morbidity. This research has assessed the knowledge and attitude of the new residents about CPR, and for answering to this question: "Is the CPR workshops necessary for all of the new residents in the beginning of their courses". All of the 506 new residents were examined simultaneously in 2 separate years with a questionnaire consist of 50 questions about their CPR secence and skills and 8 questions about their attitude in CPR. These informations were analyzed by SPSS and EPI6 softwares. The mean correct answers were 55%±11.8. The best results were about arrythmias (68.6%) and airway management (63.6%) and the worst were about IV access (43.1%) and pediatric CPR (31.5%). These findings were similar in 2 sequential years. Their knowledge had significant relation with sex (P=0.002), their original university (P=0.031), their residency course (P=0.024) and their residency reception scores (P<0.001). Males and knowledge more than females. The max scores were from Kerman (62%) and Beheshti universities (60.5%) and the min score were from Hamadan (48%) and Kashan universities (37%). The orthopedic (62.5%) and urologic residents (61.6%) had the most knowledge and the gynecology residents (53.8%) had the least. The knowledge had no relation with the time of graduation. About their attitude in CPR: Their knowledge was moderate (65.8%), their abilities was moderate (58%) and their education about CPR in MD course had been low (51.5%). Their references for education had been individual studies (74.6%), CPR workshop had not been condected in the most universities (92.7%). knowledge about CPR is low (55.8%) and must be 100%. In advanced centers, continuous educations in CPR is essential. Residents with low scores have accepted in courses that have more CPR situations. Difference in knowledge of residents from different universities, show the different educations. Primary knowledge was low and after years, this is lower. Attitude of residents show the low knowledge, low ability, low education in MD, courses.